Towards measuring intonation quality of choir recordings: A case study on bruckner's locus iste - Weiß, Christof; Schlecht, Sebastian; Rosenzweig, Sebastian; Müller, Meinard (Proceedings of the 20th International Society for Music Information Retrieval Conference, ISMIR 2019, 2019)
Unaccompanied vocal music is a central part of Western art music, yet it requires excellent skills for singers to achieve proper intonation. In this paper, we analyze intonation deficiencies by introducing an intonation cost measure that can be computed from choir recordings and may help to assess the singers' intonation quality. With our approach, we measure the deviation between the recording's local salient frequency content and an adaptive reference grid based on the equal-tempered scale. The adaptivity introduces invariance of the local intonation measure to global intonation drifts. In our experiments, we compute this measure for several recordings of Anton Bruckner's choir piece Locus Iste. We demonstrate the robustness of the proposed measure by comparing scenarios of different complexity regarding the availability of aligned scores and multi-track recordings, as well as the number of singers per part. Even without using score information, our cost measure shows interesting trends, thus indicating the potential of our method for real-world applications.
CRIS-Team Scopus Importer:2023-11-06